Recepcija gregorijanskega korala v ljubljanski škofiji v dolgem 19. stoletju - Nagode, Aleš (Muzikološki zbornik, 2023)
The article outlines the reception of Gregorian chant in Slovenia in the nineteenth century. Using the scarce sources, it describes the situation in the first half of the century and the impact of the first sporadic attempts at a historicist reform. It traces in detail the growth of the Cecilian movement after 1877 and uses sources to analyse the means, content and success of its reform efforts.
Keywords: 19. st.; 19th cent.; caecilian movement; catholic sacred music; cecilijanstvo; Gregorian chant; Gregorijanski koral; katoliška cerkvena glasba; Sakralna glasba; Slovenia